Rhythms of foliage and flowering in some native woody plants - González, S. (Agrociencia Uruguay, 2003)
A floristic survey was carried out in native arboreal communities of Sierra de Rios (Cerro Largo - Uruguay) with the purpose of increasing the knowledge about the flora of the northeastern region of the country and to verify if the physiognomic differences among the arboreal formations are mainly sustained by floristic composition differences. Thirty-two sites were surveyed and classified according to their physiognomy in bosques ribereños (gallery forests), bosques de quebrada (gulch forests), bosques pantanosos (swamp forests), and bosques serranos (low mountain forests). Floristic composition was determinated on the basis of presence/ absence data. Eighty-eight tree species were detected, under 34 families. Some of these species are very rare in Uruguay and one was detected for the first time. Correspondence and cluster analyses were carried out to detect distribution patterns and grouping of sites and species. These analyses proved that physiognomic differences are not necessarily determined by clear differences in floristic composition. Great frequency variability was encountered, which hindered the identification of clear-cut clusters. Cluster analysis reveals that the similarity indexes (Czekanowski similarity index) are generally low, which might be explained by the presence of a great number of species with a very low frequency of appearance among sites.